Ecological Waves at Tourist Attractions on the Qinghai-Tibet Plateau Promote Greenness of Surrounding Vegetation - Zitao Yang; Li Tian (Land)
The unique tourism resources of the Qinghai-Tibet Plateau have created conditions for the development of ecotourism, while the existence of attractions may also have positive and negative impacts on the surrounding environment. This study defines the radiation waves that generate ecological effects as “ecological waves”, quantifies the ecological waves of attractions by buffer zone analysis of the normalized difference vegetation index (NDVI) within 20 km of 38 4A and 5A attractions on the Qinghai-Tibet Plateau in 2020, and elaborately explores the ecological effects of attractions on the surrounding environment. By combining the principle of ripple effects, it analyzes the impact of urban attractions on urban vegetation environments. The study found that attractions on the Qinghai-Tibet Plateau have a positive ecological effect on the surrounding vegetation, the positive ecological effect of suburban attractions has a distance threshold, effectively promoting vegetation greenness within a range of 6–14 km, and the ecological effect disappears beyond 14 km. In addition, applying the ripple effect model to urban attractions and city centers (Xining and Lhasa), the results indicated that among the five urban attractions in Xining, Kumbum Monastery, Qinghai Tibetan Culture Center, and Country Farming Ecological Park (with distance restrictions of 2–20 km) have significant positive ecological effects within the built-up area, while the ecological effects of Qinghai Province Museum and Qinghai-Tibetan Plateau Safari Park are not significant. The positive ecological effects of the five urban attractions in Lhasa within the built-up area are not significant, and different attractions have different distance thresholds for ecological effects. Furthermore, this study found that attractions in Qinghai have a better ecological foundation around them than attractions in Tibet, making them more suitable for the development of ecotourism. This study has opened up a new perspective on the ecological effects of attractions and provided scientific references for the development of ecological tourism in the Qinghai-Tibet Plateau.